Japanese modernisation and Mingei Theory : cultural nationalism and oriental orientalism - Kikuchi, Yūko (RoutledgeCurzon, 2004)
This new interpretation of the Mingei movement will appeal to scholars of Japanese art history as well as those with interests in cultural identity in non-Western cultures.